MENULIS SEBAGAI BENTUK PELESTARIAN BUDAYA LOKAL - Santi Susanti (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Sundanese is a part of local culture that contribute to the wealth of Bahasa Indonesia, as well as an identity for the Sundanese whose own the language. Preservation of its existence needs to be done in order to avoid its lost by cultural dynamic changes of society. Concerns about not using Sundanese as a communication tool emerges, as data showed the decline of Sundanese speakers and the fact that a number of Sundanese families no longer teach Sundanese to their children. To keep the identity remain to exist, the use of Sundanese in communication as a part of local culture should be continued. The role of language owners in maintaining its use is very meaningful. One of the efforts made through written works about Sundanese and/ or written in Sundanese. This paper aims to reveal the role of writers in Bandung preserve Sundanese culture through writing. This research uses qualitative-phenomenology method and data obtained through in-depth interviews with 8 informants, observation, and literature study. Informants were chosen through purposive sampling technique. The results show, preservation of Sundanese culture through Sundanese writing is driven by idealism as the language owner to maintain the Sundanese existence and still known by next generation. Writing forms and media are selected vary, according to the ability of authors to deliver it.